Unitarianism and Social Reconciliation in North and South - Ipek Kotan Yiğit (Ideas: Journal of English Literary Studies)
Elizabeth Gaskell’s North and South (1855) is traditionally categorized as an industrial novel. The protagonist Margaret Hale is the daughter of an Anglican clergyman living in the South of England who relocates to the industrial North with her family after her father resigns from the Church due to religious differences. There in the northern town of Milton, Margaret witnesses the new reality of an industrializing England: she sees the mill-owners and the millworkers locked in a struggle. Although class-oriented criticism of the novel often highlights its depiction of class relations between the masters and the workers, the novel is in fact equally, if not more, invested in the integration of the two contending ruling classes – the old gentry and the new bourgeoisie, and this integration is developed through Margaret’s encounter with the town of Milton and her eventual marriage to Mr. Thornton, the industrialist. Although this point has been overlooked relative to the critical focus placed on relations between the ruling class and the workers, it is nonetheless an important element of the narrative and, moreover, a distinctly Unitarian one. This integration is a Unitarian interest, less related to points of principle or doctrine but closely connected to social reality. The new ruling class emerging from the industrial towns of the North and the Midlands, among whose ranks Unitarians were over-represented, demanded access to the social capital and prestige of the old order. As such, the marriage plot in the novel is also an argument for Unitarian integration in the establishment.